Measures heart in height native - Miranda, Artemio (1944)
A preliminary investigation has been carried out concerning the values corresponding to the transverse diameter of the heart, the frontal area of the cardiac silhouette and the diameter of the aortic arch. These measurements have been determined in radiographs of the chest, taken at 2 meters (6 feet) distance, in 107 subjects living at sea level and in 250 residents of Morococha, at 4,540 meters of altitude. All the subjects were healthy males, of en age between 18 and 35 years. The prediction of the normal values corresponding to these measurements has been obtained from the tables and nomograms of Ungerleider and Clarck. The results obtained at sea level demonstrated that it was possible to utilize these comparative values: 94.5 % of the transverse diameter measurements tell within the normal variations given by Ungerlayder and Clarck; the frontal area measurements showed wider variations from the predicted values, this probably due to the lack of precise methods in determining the outline of the superior and inferior borders of the heart. Of the 250 men studied at high altitudes, 66.8 % showed an increase in the transverse diameter of the heart; the increase varied between 11 and 30 % over the normal sea level measurements, with a mean value of 21 %. In 77.6 % of the high altitude subjects the frontal area of the cardiac silhouette had a greater value than in the sea level residents; the average increase was 36.4 %. It was also found an increase in the aortic arch diameter in most of the high altitude residents; the greatest increase, over the sea level, was 42 %. Finally, 65 % of the radiographs taken at the high altitudes showed an accentuation of lung markings and a definite prominence of the pulmonary conus.